Application of the power of attorney in the law of guarantee against fixed objects in Indonesia - Agustan, Leny; Yaswirman, Yaswirman; Azheri, Busra; Fendri, Azmi (Linguistics and Culture Review, 2021)
The power of attorney in the Civil Code concerning the granting of power, which is an agreement, so that a binding principle applies to both parties. In addition to the principle of binding consensus also for them the principle of goodwill, that the parties in making agreements must have goodwill. In its development, the power of attorney, especially in business law and the world of a notary, gave birth to the name of absolute power, which then in the field of a notary is known to be contained in the power of attorney imposes dependent rights (SKMHT). This SKMHT arises from the existence of a principal agreement between the debtor and the credit against the material guarantee. SKMHT is a power of attorney that is specific to one legal action only and is an irrevocable power of attorney.